Formulation and Evaluation of Beclomethasone Dipropionate Loaded Niosomal Gel for Topical Use - Birajdar, Mahesh; Sarda, Rohit; Tiwari, Shradha; Jadhav, Dnyaneshwari; Sonvane, Sameep; Shivnechari, Prakash; Satpute, Kranti (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: The present study focuses on the formulation and evaluation of a niosomal gel containing beclomethasone dipropionate for topical delivery, with the objective of enhancing skin permeability and achieving sustained drug release. Niosomes, which are spherical vesicles composed of non-ionic surfactants, offer several advantages over conventional drug delivery systems, including higher drug loading capacity, controlled release, and reduced systemic side effects. Materials and Methods: In this study, niosomes were prepared using the thin-film hydration technique by optimizing the ratios of Span 60 and cholesterol. The prepared niosomal dispersions were subsequently incorporated into a Carbopol-based gel and subjected to comprehensive evaluation. Evaluation Parameters: Various parameters, including vesicle size, entrapment efficiency, pH, spreadability, drug content, and in vitro drug release, were assessed. Results/Conclusion: The results demonstrated that the optimized niosomal gel possessed favorable physicochemical properties, exhibited sustained drug release, and showed significant potential as an effective topical drug delivery system.
Keywords: Carbopol gel; Controlled Release; Niosomes; Non-ionic Surfactants; Thin-Film; Hydration Method; Topical Drug Delivery